Total Quality Management (TQM) in Madrasah Aliah Mazro'atul Huda Karanganyar - Aifiatur Rohmaniyah (Tarbiyah Departement collaboration with AMCA, 2020)
The implementation of TQM culture at MA Mazro'atul Huda Karanganyar was carried out with the aim of improving the quality of madrasas, starting to frequently communicate actively with internal and external customers in the form of regular monthly meetings and light discussions, completing customer facilities, issuing policies according to data, giving trust full of internal customers in fulfilling duties, action on improvement. Obstacles in implementing TQM culture come from internal and external customers in the form of rejection of the policies issued, and student backgrounds that affect motivation in learning. Then the result of the application of the TQM culture is the issuance of an A accreditation certificate by BAN SM, there is recognition of pride from the guardians of students and the community of graduate users of children or madrasah graduates in society, the emergence of solidarity and discipline from internal customers. This proves that TQM can improve the quality of MA Mazro'atul Huda Karanganyar.